2017
DOI: 10.18844/prosoc.v4i4.2595
|View full text |Cite
|
Sign up to set email alerts
|

Investigating of the subjective well-being of gifted adolescents

Abstract: As highly gifted adolescents both maintain their personal development salubriously while coping with the differences caused by being highly gifted and adapt to quick changes in every field of teenage life, they are thought to be a group that has to be specially emphasized. This study aims to analyze the subjective well-being in terms of giftedness, gender and age. The participants of the study consisted of 80 students studying in the 5-6-7-8th grades of secondary schools in Ankara. 32 of the students were diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…On one hand, a number of studies argue that gifted children tend to have higher estimates of psychological well-being than children who fall within the normal range of ability. These results were confirmed for American, Turkish and Russian samples (Boazman, Sayler 2011;Nail, Evans 1997;Tatli 2017;Rodenko 2010), as well as by the metanalytical study by Timothy Jones (Jones 2013). However, other studies revealed a lower psychological well-being score in gifted children (Fouladchanga, Kohgard, Salah 2010;Vedikova, Kalyagina 2018).…”
Section: Introductionmentioning
confidence: 55%
“…On one hand, a number of studies argue that gifted children tend to have higher estimates of psychological well-being than children who fall within the normal range of ability. These results were confirmed for American, Turkish and Russian samples (Boazman, Sayler 2011;Nail, Evans 1997;Tatli 2017;Rodenko 2010), as well as by the metanalytical study by Timothy Jones (Jones 2013). However, other studies revealed a lower psychological well-being score in gifted children (Fouladchanga, Kohgard, Salah 2010;Vedikova, Kalyagina 2018).…”
Section: Introductionmentioning
confidence: 55%
“…On the one hand, a number of studies argue that gifted children tend to have higher estimates of psychological wellbeing than children with regular levels of abilities. The results were confirmed for American, Turkish and Russian samples [7,8,9,10], as well as by metaanalitic studies [11]. On the other hand, other studies revealed a decline in psychological wellbeing of gifted children [12,13].…”
Section: Introductionmentioning
confidence: 66%